Besedotvorni tematski blok na petnajstem mednarodnem slavističnem kongresu v Minsku (2013) - Voršič, Ines; Stramljič Breznik, Irena (Slavia Centralis, 2020)
The authors of the article report on the 15th International Slavic Congress, which took place from 20 to 27 August 2013 in Minsk.
Keywords: report; slavistic; word-formation